A Theoretical and Practical Approach to Exponential Relation between Innovation and Sustainable Development - Ceko, Enriko; Mulita, Reis; Jaupaj, Artur (Problemy Ekorozwoju, 2024)
A Aside from the political, geographic, economic, legal, social, and cultural problems that every nation, state, and government faces, it is evident that sustainable development is the key to sustainability, progress, and improving the quality of life. Achieving SDG targets has been seen as the primary trend for the past 15 years and the foreseeable future. In this direction, with an eye towards the fifth industrial revolution, innovation has been viewed as one of the primary production variables, along with land, labor, capital, and entrepreneurship, to help address current and future difficulties facing humanity. This study aimed to shed light on the connections between innovation and sustainable development. To test Hypothesis H1, which states a positive solid relationship between the SDG Index and ISO 9001 Index, we conducted a statistical analysis using regressive analysis between the Sustainable Development Goals Index and Innovation Index. This was done to compare the results to Hypothesis H0, which suggests no such relationship exists. The research's findings indicate that scientific management of the factors of production opens up possibilities for long-term sustainable development, ensuring the prosperity of society and everyday life for future generations, encouraging economic growth, and improving the quality of life without endangering the environment. Innovation, embodied in the ISO 56000 family of standards, is applied as an efficient and effective tool, which is urgently needed. The overall conclusion of the study – which also serves as a practical and social contribution to the field – is that, to achieve and sustain sustainable development scenarios, all interested parties – individuals, public and private institutions, decision-makers, and civil society – should look forward to ensuring that the SDG and innovation are built and maintained. Innovation principles can be applied as effective and efficient tools.